New Insights Into the Long Non-coding RNA SRA: Physiological Functions and Mechanisms of Action - Sheng, Liang; Ye, Lan; Zhang, Dong; Cawthorn, William P.; Xu, Bin (Frontiers in Medicine, 2018)
Long non-coding RNAs (lncRNA) are emerging as new genetic/epigenetic codes in almost all physiological functions. Here, we focus on new insights of the long non-coding steroid receptor RNA activator SRA in physiological functions on regulation of gene expression, cell cycle and differentiation, as well as cause of diseases and molecular mechanism of its action. We discuss that SRA exerts its function as an RNA coactivator in nuclear receptor signaling in regulation of steroidogeneis, adipogeneis and myocyte differentiation, and tumorigenesis in breast and prostate cancers, as well as hepatic steatosis through several signaling pathways. Genome-wide analysis reveals that SRA regulates hundreds of target genes in adipocytes and breast cancer cells, and binds to thousands of genomic sites in human pluripotent stem cells. The unique of SRA stem-loop secondary structure and modification are important for its function. Recent studies indicate that SRA functions as a molecular scaffold and forms networks with numerous coregulators and chromatin-modifying regulators in both activating and repressive complexes. In addition, we highlight the various SRA isoforms and mutations relevant to their clinical defects. Finally, we discuss the future directions for molecular mechanism of SRA action and the diagnostic and therapeutic potentials.